Epididymal melanotic neuroectodermal tumor of infancy: A rare cause of scrotal mass in an infant. Issue 2 (5th November 2018) - Burton, Kirsteen R.; Ngan, Bo‐Yee; Navarro, Oscar M.
Abstract: Melanotic neuroectodermal tumor of infancy (MNTI) is a rare, benign neoplasm of neural crest origin more commonly seen in the craniofacial region. We report a case of MNTI of the epididymis in a 6‐month‐old male child with emphasis on the sonographic appearance which has not been previously described. In this case, the mass was inseparable from the testicle and therefore the differential diagnosis considered both extratesticular and intratesticular masses. MNTI should be added to the differential diagnosis of scrotal masses, particularly if they present in a child younger than 12 months of age.